Symptoms and postoperative complications in ambulatory pediatric surgery - Gómez Buitrago, Luz; Rodríguez, Jhon Jairo; Valencia Ríos, Juan Felipe (Universidad y Salud, 2012)
Currently, a large percentage of surgical procedures are performed in day-case surgery programs. Postoperative symptoms most often reported by medical literature in ambulatory surgery include pain, nausea, vomiting, symptoms and complications that occur in the first 48 hours after the completion of surgical or diagnostic procedure in ambulatory surgery program at Hospital Infantil Universitario from Manizales, Colombia, between March and July2009, based on the information of symptoms and complications of 720 pediatric patients scheduled for surgery in the first 48 hours postoperatively. The results show that from 1170 procedures performed in general surgery, otolaryngology, ophthalmology, dentistry, radiology, urology, orthopedics and plastic surgery, 720 met the inclusion criteria. The most common symptom was pain in otolaryngology procedures (47%) and urogenital (43%), followed by nausea and vomiting (14, 6%) in otolaryngology procedures. There were 11 cases of unplanned consultation for surgical site pain, dehydration and fever. Pain was the most important symptom.